MATERIALE DE REGENERARE OSOASA-XENOGREFELE - Irina Alexandra Simion; Norina Consuela Forna (Romanian Dental Association for Education, 2016)
The study aimed at individualizing the various types of xenografts used within the therapeutic algorithm of implanto-prosthetic rehabilitation. The identification by clinical and paraclinical methods of the particularities of the clinical case which requires an implant is an essential condition of targeted therapy, but also a starting point for the rigorous selection of the dental materials involved and the exigencies related to the recreation of a highfidelity morphology. The study lot comprised a number of 7 patients (aged between 30 and 82), reuniting various clinical entities in the field of dental prosthetic. The patients underwent complex clinical and paraclinical examinations which focused on a series of criteria that led to correlative aspects, with a profound impact regarding the periodontal pathology, characterized by the multiple facets of a complex clinical picture.Related to the subject approached, we detailed 2 clinical cases in whose implant rehabilitation algorithm xenografts were used.Xenografts are successful materials in various types of augmentations, contributing to the implant therapeutic success, together with a thorough clinical and paraclinical evaluation of the implant candidate and a thorough compliance with the surgical procedures